The Impact of Age on Propofol Requirement for Inducing Loss of Consciousness in Elderly Surgical Patients - Hua Yang; Hui-Min Deng; Hai-Yan Chen; Shu-Heng Tang; Fang Deng; Yu-Gang Lu; Jin-Chao Song (Frontiers Media S.A., 2022)
It is generally accepted that geriatric patients are more sensitive to propofol than adults; thus, a dose-adjusted propofol is recommended for these patients during the induction of anesthesia. However, for patients aged 75 years and over, established guidelines for propofol induction doses do not provide dose references. To this end, we observed 80 surgical patients (female 39, male 41, American Society of Anesthesiologists physical status score I ∼ II) to access the appropriate dose of propofol for inducing loss of consciousness (LOC). Accordingly, patients were subdivided into group A (20 patients, 45-64 years), group B (20 patients, 65-74 years), group C (20 patients, 75-84 years), and group D (20 patients, ≥ 85 years). All patients received propofol (at a rate of 0.3 mg/kg/min) alone for inducing LOC, which was defined by loss of both eyelash reflex and verbal response. Compared with group A, the propofol requirement for LOC in Group B, C and D decreased by 14.8, 25.2 and 38.5%, respectively. Bivariate linear correlation analysis showed that propofol requirement was negatively correlated with age. After adjusting for potential confounders, age was still an independent factor affecting propofol requirement. In conclusion, the propofol requirement for inducing LOC decreased significantly in elderly patients. We demonstrated that age was an independent factor impacting propofol requirement for LOC during the induction of general anesthesia, implying that the propofol dose for anesthesia induction should be further reduced in elderly surgical patients, especially those aged 75 years and over.